Treatment of Renal Cell Carcinoma with 2-Stage Total en bloc Spondylectomy after Marked Response to Molecular Target Drugs. (17th July 2013) - Inoue, Yasuhiro; Takahashi, Hiroshi; Yokoyama, Yuichiro; Iida, Yasuaki; Fukutake, Katsunori; Takamatsu, Ryo; Nakamura, Kazumasa; Wada, Akihito
Abstract : Metastatic renal cell carcinoma of the bone occurs at a high rate, and the prognosis is poor. In general, total en bloc spondylectomy is considered when there is only one vertebral metastasis and the primary disease is treated. However, palliative surgery is selected when the primary disease is not being treated or metastasis occurs to an important organ. We encountered a patient in whom lung and vertebra metastases were already present at the time of the first examination at our department and the prognosis was considered poor. However, molecular targeted therapy was markedly effective and enabled 2-stage total en bloc spondylectomy. As of one year after total en bloc spondylectomy, the condition has improved to cane gait, and surgery for lung metastasis is planned. Molecular target drugs might markedly change the current therapeutic strategy for renal cell carcinoma.